A prospective study on maternal near miss cases at a tertiary care hospital - Das, Karuna Kanta; Das, Sasindra Kumar; Das, Dhritimala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnant women’s health status is not only reflected by mortality indicators alone hence the concept of Severe Acute Maternal Morbidity (SAMM) is appropriate for present health providing system. It helps to evaluate the quality of obstetric care in a particular institute. The main objectives of the study were to find a) Incidence of MNMM; b) Disorders underlying MNMM; c) Socio-demographic variables among MNMM; d) Facilities and skills needed to handle these near miss situations. Methods: A prospective hospital-based study was conducted in the department of obstetrics and gynaecology, Gauhati Medical College and Hospital, Guwahati during the period 1st June 2018 to 31st May 2019. Cases were identified based on maternal near miss operational guidelines December 2014. Results: Out of 16222 live births, 241 near miss cases were identified during the study. The maternal near miss incidence ratio is 14.86 per 1000 live births. The maternal near miss to maternal mortality ratio is 2.025. Most common cause of MNMM is hemorrhage (48.54%) followed by hypertension (19.5%), anemia (13.28%), sepsis (10.37%), cardiac dysfunction (6.2%), liver dysfunction (0.83%), renal dysfunction (0.83%) and respiratory dysfunction (0.41%). Conclusions: The large magnitude of MNM cases may be attributed to improper management of obstetric emergencies at the referring hospitals, poor referral practices, inefficient transport system, limited availability of blood products and poor utilization of health care services at the peripheral hospitals. In our tertiary center, with the help of multidisciplinary action to all the near miss cases we can reduce maternal mortality to a great extent.